Pengaruh Pertumbuhan Ekonomi, Pendapatan Asli Daerah Dan Dana Alokasi Umum Terhadap Pengalokasian Anggaran Belanja Modal Tahun 2013-2015(Studi Empiris Kabupaten/Kota Seluruh Provinsi Jawa Tengah) - Setyawati, Siti, Fauzan, S.E., M.Si., Akt., CA (2017)
This study aimed to examine the effect of Economic Growth, Regional Income and General Allocation Fund toward Allocation of Capital Expenditure Budget in the Regency and City of the Central Java in 2013 - 2015. In this study the researcher using Saturated Sampling Technique as a sampling method where all of the population will be used as a sample of research. Sample that used in this study is 104 APBD realization reports in the Regency / City of the Central Java in 2013 - 2015. The dependent variable is Capital Expenditure and the independent variables are Economic Growth, Regional Income and General Allocation Fund. The data analysis method is use multi- linear regression analysis method. From these results it can be concluded that the Economic Growth does not influence to the Allocation of Capital Expenditure Budget, meanwhile Regional Income and General Allocation Fund have influence to the Allocation of Capital Expenditure Budget.